MODEL HUBUNGAN HUKUM DAN SISTEM KERJA PETANI MILLENNIAL BERBASIS KEBENARAN FORMAL - Prasetyo, Rudy Wahyu; Wijayanti, Asri; M. Zamroni (Penerbit Universitas Atma Jaya Yogyakarta, 2025)
Millennial farmers are a farmer regeneration program. Millennial farmers are legal subjects in industrial relations. The success of the millennial farmer program can be hampered if the agreement on which the legal relationship is based is blurred. The status of legal relationships related to millennial farmers is not enough just a work relationship, another form is needed. This research takes the problem is how the legal relationship can occur in the work system of millennial farmers, how formal truth can be the basis for settlement in the event of a dispute, and how the concept of formal truth is used as a basis for making autonomous rules for millennial farmers. This normative legal research uses a statute approach. The conclusion of this study is that legal relationships can occur in the work system of millennial farmers, consisting of employment relationships, apprenticeships, leases, debts and receivables, buying and selling, cooperation or partnerships, and relationships in groups. Formal truth, which can be the basis for settlement in the event of a dispute, is based on civil procedure law. The concept of formal truth that is used as the basis for making autonomous rules for millennial farmers is the truth based on the substance and procedures in the agreement on which the legal relationship is based.